Halal Industry Based on Local Culture in the Production Management of Griya Batik Mas Pekalongan - Hanif Ardiansyah (GREENOMIKA, 2024)
Griya Batik Mas Pekalongan is one of Pekalongan's well-known batik industries. This industry also uses its own waste management system. The research carried out aims to find out how batik production is managed at Griya Batik Mas Pekalongan and to find out whether the batik industry in Griya Batik Mas Pekalongan can be said to be a halal industry or not. The type of research is qualitative with a field research.  Researchers followed the steps of data analysis as proposed by Miles and Huberman. The stages of the analysis include: (1) data collection; (2) data reduction; (3) data presentation; and (4) verification / drawing conclusions. The results and conclusions of this study are that the production management process at Griya Batik Mas Pekalongan has implemented the management function well. From planning, organizing, implementing and ending with controlling/supervision. The production process at Griya Batik Mas Pekalongan is also included in the halal local culture industry. Because the batik making process and waste treatment at Griya Batik Mas Pekalongan has implemented a wastewater treatment plant (IPAL) system that has been organized to filter batik production waste.